A checklist of Polygala (Polygalaceae) in the Flora of Southern Africa region with notes on types - Figueiredo, Estrela; Smith, Gideon F.; Paiva, Jorge (Phytotaxa, 2013)
As part of a revision of Polygala in the Flora of Southern Africa region, the types of all the names relevant for the region were assessed. A catalogue of the names and their types is provided along with information on the availability of online images of these types. For 22 accepted taxa, no images of the types of the names are available online. Twenty lectotypes are designated here.